Levels of some heavy metals in vegetables from artisanal mining sites of Dilimi River, Bukuru and Barkin Ladi North Central Nigeria: any public health concern? - Orish Ebere Orisakwe; Emmanuel Ayuba Dagur; Herbert Orji Chidi Mbagwu; Nnaemeka Arinze Udowelle; Samuel James Offor (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. North Central Nigeria is the food basket of Nigeria but is also known for its artisanal mining with attendant public health consequences which is hitherto unquantified. Vegetables grown close to these mining sites may be contaminated with heavy metals. Objective. This study has estimated health risk associated with heavy metals HM (Cd, Cr, Cu, Zn, Se and Ni) in vegetables harvested inform the mining areas of Dilimi, Bukuru and Barkin Ladi by calculating the Daily intake, Target Hazard Quotient (THQ), Hazard Index (HI) and the Cancer risk (CR) for adults and children in the local population. Material and methods. Vegetable, soil, irrigation water and sediments samples were collected, digested, ashed and analyzed for HM using an Atomic Absorption Spectrometer (AAS). Results. The concentration of heavy metals in vegetables were in the order Cd < Se < Cr < Cu < Ni < Zn. There were higher HM levels in soil than vegetables samples. The daily intake of HM from vegetable consumption decreased in the following order Cd < Se < Cr < Cu < Ni < Zn. At least 62.5% of vegetable samples had THQ values > 1 in Dilimi, Bukuru and Barkin ladi (Adults) while 13% of vegetable samples had THQ values > 1 in children. The THQ of nickel ranged from 0.38-2.73 and 0.21-1.53 in adults and children respectively. The bio-concentration factor ranged from 0.026-7.52, 0.01-0.36 and 0.0011-1.23 in Dilimi, Bukuru and Barkin Ladi respectively for all the studied heavy metals. The cancer risk values ranged from 0.011-0.04 and 0.00066-0.02 across all the studied areas for adults and children respectively. HI values for adults were all >1 and also the total cancer risk was above the acceptable range of 10-4. Conclusion. Since THQ is > 1 in most of the samples, HI values > 1 for adults in all the vegetable and cancer risk above the acceptable limit consumption of vegetables from the study areas is not free of risk.